PENGUJIAN WEEK-FOUR, MONDAY, FRIDAY DAN EARNINGS MANAGEMENT EFFECT TERHADAP RETURN SAHAM - Ambarwati, Sri Dwi Ari (Jurnal Keuangan dan Perbankan, 2009)
The Purpose of this research was to know the empirical impact of days of the weekeffect to daily stock return. It used data of LQ-45 manufacturing companies listed during 2006in Indonesian Stock Exchange and was analyzed using multiple regression through originwithout intercept and dummy variables. The findings were: 1) there was impact in days of theweek effect phenomenon with stock price, it meant the lowest return was on Monday and thehighest return was on Friday; 2) there was no significantly positive impact between week-foureffect with stock price. It meant liquidity could not influence trading activity; 3) there was nosignificantly positive impact between Friday effect and stock price and 4) there was nosignificantly positive impact between Earnings Management effect and stock price. It meantEarnings Management in April could not influence daily stock return.